2018
DOI: 10.1007/s12035-018-1380-6
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Preconditioning Induces Genomic and Metabolic Adaptations within the Long-Term Window of Cerebral Ischemic Tolerance Leading to Bioenergetic Efficiency

Abstract: Neuroprotective agents administered post cerebral ischemia have failed so far in the clinic to promote significant recovery. Thus, numerous efforts were redirected towards prophylactic approaches such as preconditioning as an alternative therapeutic strategy. Our lab has revealed a novel long-term window of cerebral ischemic tolerance mediated by resveratrol preconditioning (RPC) that lasts for two weeks in mice. To identify its mediators, we conducted an RNA-seq experiment on the cortex of mice two weeks post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…Stilbenoids possess both the cis and trans forms, and the trans form is found to be more bioactive and stable [222]. In total, 7 stilbenoids are reported in the past 10 years for their neuroprotective activity in ischemic stroke, that is, resveratrol [45,[223][224][225][226][227][228][229][230][231][232][233][234][235], polydatin (resveratrol-3-β-D-glucoside) [236,237], malibatol A (a resveratrol oligomer) [88,238], oxyresveratrol [239], mulberroside A (oxyresveratrol-3,4 ′ -diglycopyranoside) [240], pterostilbene [241], and 2,3,5,4 ′ -tetrahydroxystilbene-2-O-β-D-glucoside [242]. Their neuroprotective mechanisms are explained in Table 3, and the chemical structures of the extensively studied stilbenoids are shown in Table 4.…”
Section: Stilbenoids Stilbenoids Refer To a Class Of Compounds That Have Two Aromatic Rings Connected By An Ethene Bridgementioning
confidence: 99%
“…Stilbenoids possess both the cis and trans forms, and the trans form is found to be more bioactive and stable [222]. In total, 7 stilbenoids are reported in the past 10 years for their neuroprotective activity in ischemic stroke, that is, resveratrol [45,[223][224][225][226][227][228][229][230][231][232][233][234][235], polydatin (resveratrol-3-β-D-glucoside) [236,237], malibatol A (a resveratrol oligomer) [88,238], oxyresveratrol [239], mulberroside A (oxyresveratrol-3,4 ′ -diglycopyranoside) [240], pterostilbene [241], and 2,3,5,4 ′ -tetrahydroxystilbene-2-O-β-D-glucoside [242]. Their neuroprotective mechanisms are explained in Table 3, and the chemical structures of the extensively studied stilbenoids are shown in Table 4.…”
Section: Stilbenoids Stilbenoids Refer To a Class Of Compounds That Have Two Aromatic Rings Connected By An Ethene Bridgementioning
confidence: 99%
“…Recently, proteomic and transcriptomic studies paved a new way of looking for a cause of neurons' delayed death or survival after IR episodes and for candidates for ischemic brain treatment [20]. Moreover, metabolomics was applied to investigate cerebral injury and protection in mice and rat models of brain ischemia [21][22][23][24][25]. Research has been carried out using various metabolomic techniques and in various models of global ischemia and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, studies confirmed that OGD/R induced bEND3 cerebrovascular endothelial cell edema was associated with monocyte chemoattractant protein and intracellular Ca 2+ overload, while resveratrol could maintain mitochondrial MMP by inhibiting ROS and elevated Ca 2+ ions, thus improving hypoxic brain edema (Panickar et al, 2015). Excitingly, recent study has further demonstrated that the antianoxic brain protection of preadministrated resveratrol may be related to consolidating mitochondrial tolerance to anoxia and increasing VDAC level and energy synthesis (Khoury et al, 2019). However, on the contrary, picroside II could interdict release of pro-apoptotic factor Endo G into the nucleus driven by MPTP opening, ROS production and VDAC1 protein expression (Li S. et al, 2018).…”
Section: Monomers and Molecular Mechanisms In Regulating Mptp Opennesmentioning
confidence: 94%